KORELASI PENGETAHUAN DAN SIKAP KELUARGA TERHADAP TINDAKAN PENCEGAHAN DEMAM BERDARAH DENGUE - Awaluddin, Awaluddin (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
The incidence of DHF has increased over the last 3 years. This study aims to analyze the correlation of knowledge and attitudes of family toward dengue hemorrhagic fever prevention. This research is a quantitative, analytic observational design with cross sectional approach. This research was conducted in Tampan subdistrict working area of Sidomulyo Health Center in Pekanbaru, on 1-13 August 2016. The sampling technique used was total sampling with 33 samples. Data collection using questionnaires. Data analysis using Chi square. The results of this study indicate the relationship of family knowledge with dengue hemorrhagic fever preventions with a probability value of 0.007 (p value <0.05) and there is a relationship of family attitudes with dengue hemorrhagic fever preventions with a probability value of 0.009 (p value <0.05). It is expected that further research on the effect of effective education methods in improving the knowledge and attitude of the community in the prevention of DHF.